Teach the torches to burn : a Romeo & Juliet remix - Roehrig, Caleb (Remixed classics., 2023)
In Verona, Italy, gay teens Romeo and Valentine discover first love amid a bloody, centuries-old feud, putting themselves in danger of losing each other forever.